Effects of Rate of Reinforcement and Rate of Change on Choice Behaviour in Transition - Mazur, J.E. (Quarterly Journal of Experimental Psychology Section B: Comparative and Physiological Psychology, 1997)
In two experiments with pigeons, a single variable-interval schedule assigned reinforcers to two response keys on a percentage basis. The percentage of reinforcers assigned to each key was changed every few sessions, and subjects' choice responses were recorded before and after each change. In Experiment 1, the overall rate of reinforcement was varied across conditions The pigeons' choice responses adapted more quickly to a change in the reinforcement percentages when the overall reinforcement rates were higher, but acquisition rates varied by only about a factor of 3, whereas reinforcement rates were varied by about a factor of 9. In Experiment 2, the reinforcement percentages changed about every 8 sessions in Phases 1 and 3, but every 1 or 2 sessions in Phase 2. Pigeons' choice responses adapted to a change in reinforcement percentages more quickly in Phase 2 than in Phases 1 and 3. The results from both experiments pose difficulties for several prominent models of transitional choice behaviour. The results suggest that each successive reinforcer has more impact on a subject's subsequent choice behaviour when the overall rate of reinforcement is lower and when the reinforcement contingencies have changed frequently in the recent past.
Keywords: *Choice Behavior; *Reinforcement, Psychology; Animals; Behavior, Animal; Choice Behavior; Columbidae; Reinforcement (Psychology); animal; animal behavior; article; comparative study; decision making; dept.psy; pigeons and doves; reinforcement; ⛔ No DOI found

The affective nature of Mother–Adolescent communication concerning sexuality and conflict - Kahlbaugh, Patricia E; Lefkowitz, Eva S; Valdez, Patricia; Sigman, Marian (Journal of Research on Adolescence, 1997)
This 2-year longitudinal study examined the affective nature of communication between mothers and adolescents from early to mid-adolescence. Eleven-to 16-year-old adolescents and their mothers were videotaped while engaging in conversations about everyday topics, dating and sexuality, and conflicts. Nonverbal displays of affiliation, embarrassment, and contempt were found to be fairly stable across conversations, across members of the same dyad, and across time for the mothers. However, there were some effects of conversational topic in that adolescents displayed less affiliation in the conflict conversation than in the other conversations during the 1st session. In addition, boys displayed more contempt when talking about dating and sexuality than about conflicts. Over the 2-year period, the level of affiliation decreased for adolescents, and maternal conversational dominance increased. In all conversations and at both time periods, adolescents displayed more embarrassment and contempt and less affiliation than did mothers. Both maternal and adolescent levels of affiliation during the conversations in the 1st session predicted degree of satisfaction with certain family characteristics expressed in the 2nd session. Copyright © 1997, Lawrence Erlbaum Associates, Inc.
Keywords: dept.psy

Choice, delay, probability, and conditioned reinforcement - Mazur, James E (Animal Learning & Behavior, 1997)
The hyperbolic-decay model is a mathematical expression of the relation between delay and reinforcer value. The model has been used to predict choices in discrete-trial experiments on delay-amount tradeoffs, on preference for variable over fixed delays, and on probabilistic reinforcement. Experiments manipulating the presence or absence of conditioned reinforcers on trials that end without primary reinforcement have provided evidence that the hyperbolic-decay model actually predicts the strength of conditioned reinforcers rather than the strength of delayed primary reinforcers. The model states that the strength of a conditioned reinforcer is inversely related to the time spent in its presence before a primary reinforcer is delivered. A possible way to integrate the model with Grace's (1994) contextual-choice model for concurrent-chain schedules is presented. Also discussed are unresolved difficulties in determining exactly when a stimulus will or will not serve as a conditioned reinforcer.
Keywords: article; behavior; conditioning; decision making; dept.psy; model; nonhuman; reinforcement; theory